The motorway achievement. Volume 2, - Bridle, Ron; Porter, John, 1936 January 30- (Thomas Telford, 2002)
Produced by leading contributors to the motorway programme, 'The Motorway Achievement' tells the story of the creation of Britain's motorway network. It outlines the social history, as well as dealing with the technical challenges and how they were overcome.